Taking a LEAF out of the green lab book. (30th June 2022) - Houghton, Charlotte; Saurya, Saroj; Foster, Benjamin
Abstract : Do you want to make your research more efficient and reliable? Have you wondered whether science could be environmentally sustainable and what you can do to help bring this about?